Single Centre Evaluation of the Proposal of the European Society for Vascular Surgery Abdominal Aortic Aneurysm Guidelines to Stratify Surveillance after Endovascular Aortic Aneurysm Repair - Vanmaele, Alexander (2025)
Publisher Copyright: © 2025 The Authors